FAKTOR FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG GO PUBLIC DI BURSA EFEK INDONESIA 2011 – 2014 - Abd. Hamid (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2015)
Investors invest their funds in companies chosen in the stock market, depending on investors' perceptions of the success of the company reflected in the stock price that is assumed is the embodiment of Corporate Value measured from the market value of the company determined from the share price, the company yan go public, then the value of the company is reflected in the share price (listing price). In this study, there are three factors affecting the Company namely Capital Structure Value, which is the ratio between internal funds to fund external parties. Profitability is the Traffic Integration to generate profits used as a measure of the effectiveness of the management company's performance to predict future earnings. Ownership structure which is a ratio between the number of shares held by internal parties (employers) the number of shares held by the NII external parties (shareholders). Sample used was 100 companies from the population of companies listed on the Stock Exchange in 2011-2014, which jumlahny vary between 127-154, but not all companies consistently exist in the year 2011-2014, this research establishes a consistent 100 companies in the Stock Exchange in the year 2011 - 2014. Data of this research is secondary data from company reports in Indonesian Stock Exchange (www.idx.co.id). The results showed that: firstly, EPS (Profitability) positive effect on PBV (Value Company), second, DER (Capital Structure) a negative effect on PBV (Value Company), third, positive influence on the Ownership Structure PBV (Value Company)